Optimization of Hydroponic Growing Media Using Eco-Enzyme and Fish Waste for the Growth of Garlic Chives (Allium tuberosum) - Puspita, Siti Neni; Rahmadina, Rahmadina; Idami, Zahratul (Jurnal Biologi Tropis, 2024)
Chives are a type of vegetable that comes from the lily family (bulb plants). This plant contains vitamins B and C, carotene and sulfur components. As time goes by, planting media not only uses soil media, but also uses air media, known as hydroponics. Good nutrition for hydroponic growth is one that contains micro and macro nutrients such as eco enzyme nutrients and fish waste. This research aims to determine the growth of chive plants (Allium tuberosum) in hydroponic growing media and to find out the most effective nutrients in increasing the growth of chives (Allium tuberosum) using hydroponic growing media. Data were collected using a non-factorial randomized block design (RAK), namely with nutritional treatment P1: AB Mix (5 ml/liter of air), P2: Eco enzyme + fish waste (5 ml/liter of air), P3: Eco enzyme (5 ml/liter of air), P4: fish waste (5 ml/liter of air). Based on the research results, P3 had a real influence on plant height at 1 and 2 MST with results of 9 cm at 1 MST and 13.33 cm at 2 MST. P1 had a real influence on plant height at 3.4 and 5 MST. The leaf area index parameter P1 had a significant effect at 5 MST with a result of 9.67 cm but had no real effect at 6 MST. The values of net assimilation rate, relative growth rate, and chlorophyll content were not significantly impacted by P1. The parameters of leaf area index, chlorophyll content, relative growth rate, and net assimilation rate were not significantly affected by P2, P3, or P4.